Signaling by the Extracellular Matrix Protein Reelin Promotes Granulosa Cell Proliferation in the Chicken Follicle - Eresheim, Christine (American Society for Biochemistry and Molecular Biology, 2014)
Chicken oocytes develop in follicles and reach an enormous size because of a massive uptake of yolk precursors such as very low density lipoprotein and vitellogenin. Oocyte growth is supported by theca cells and granulosa cells, which establish dynamic and highly organized cell layers surrounding the oocyte. The signaling processes orchestrating the development of these layered structures are largely unknown. Here we demonstrate that the Reelin pathway, which determines the development of layered neuronal structures in the brain, is also active in chicken follicles. Reelin, which is expressed in theca cells, triggers a signal in granulosa cells via apolipoprotein E receptor 2 and the very low density lipoprotein receptor, resulting in the phosphorylation of disabled-1 and consecutive activation of the phosphatidylinositol 3-kinase/Akt pathway. This signaling pathway supports the proliferation of differentiated granulosa cells to keep up with the demand of cells to cover the rapidly increasing surface of the giant germ cell.